Implementasi Model Pembelajaran Kooperatif Tipe Group Investigation di Madrasah Ibtidaiyah - Marlina, Tuti; Hikmah, Devi Ismiatul; Anam, Choirul (Prodi PGMI STAI At-Tahdzib Ngoro Jombang, 2024)
This study aims to describe the implementation of learning and mathematics learning outcomes in data presentation material by applying the group investigation type cooperative learning model in VA class MI Al-Ghozali Surabaya. The subjects of this study were 16 students in VA MI Al-Ghozali's class. The research method that researchers use is Classroom Action Research with data collection techniques in the form of observation, interviews, tests and documentation. The results showed that the cooperative learning model of the group investigation type can improve student learning outcomes in mathematics learning material for presenting data. This can be proven by the analysis obtained from the results in cycle I and cycle II. The average student gain in cycle I was 78.75. Of the 16 students who took the final results test for cycle I, there were 11 students whose scores reached the KKM, which was 75. Furthermore, in cycle II, the average student score increased to 86.87 and all students had achieved the KKM score. In cycle II it experienced an average increase of 8.12. This shows that action research stopped in cycle II, because action learning in cycle II succeeded in increasing student learning outcomes.